Strategic Planning: In an Effort to Improve the Quality of Graduates at MTS Hasanah Pekanbaru - Siskawati, Zulfia; Asmarika, Asmarika (Universitas Pahlawan Tuanku Tambusai, 2023)
The goal of the research is to explore how strategic planning can be used to improve the quality of education acquired by graduates of MTs. Hasanah Pekanbaru. This type of study consists of descriptive qualitative research with a social focus. Observations, interviews, and documentation were employed throughout the data gathering process. Following that, the researchers used a variety of data processing and analysis methodologies, culminating in the data validity test. The findings of this study show that MTs. Hasanah Pekanbaru has a structured strategic plan that includes a medium-term plan, an advanced medium-term plan, and a long-term plan. Efforts are being made to improve the quality of graduates at MTs Hasanah Pekanbaru by recruiting students as inputs from graduates of SD, SD IT/MI State/Private through academic potential test scores, religious skills test scores, and UN scores, developing a learning process that is directed at mastering knowledge and skills (life skills), integrating religious values in each subject, and implementing a programme to improve the quality of educators by inviting teachers The numerous accomplishments of MTs Hasanah Pekanbaru students in a range of fields, both academic and non-academic, demonstrate the institution's high standard of educational excellence. Furthermore, a large percentage of graduates are accepted to study at Indonesia's state universities. Keywords: Strategic Planning, Graduate Quality, MTs Hasanah Pekanbaru